15 play experts' vision for a more playful future - Carissa Craven; Lisa Kosena Forbes (University of Huddersfield Press, 2023)
The current state of the world can negatively impact mental and physical health. Play has been show to be a powerful tool to help adults recover a sense of well-being; however, play is commonly excluded from adult life due to beliefs that play is childish, trivial, and a waste of time. This article reports the findings of an iterative, three-round Delphi study which created a communication process among a panel of 15 play experts to better understand a) play's definition/essence, b) play's place in society, c) the existence of the decline in play with age, d) current play advocacy efforts, and e) the overall lack of research on play in adulthood. Panelists indicated an influential component of changing adults' relationship to play is by accessing them on an emotional level. Therefore, instead of reporting the results traditionally, the data are presented as a poem which emotionally communicates the experts' dream for a better future of play.